The Determinants of User Behavior of Computer Based Transaction Processing Systems: The Case of Minimarket Employees in Padang, Indonesia - ., Yuhelmi; Dharma, Surya; Trianita, Mery; Sri Mulatsih, Listiana (International Journal of Engineering and Technology, 2018)
This study was aimed to investigate the determinants of actual use of computer based transaction processing system among employees in minimarkets in Padang, Indonesia. In addition to Perceived ease of use and perceived usefulness which are the basic models of Technology Acceptance Model (TAM), Subjective norm was conceptualized as an external variable that affecting Technology Acceptance among users of transaction processing system. In total, 246 employees participated in this study. The results show that the perceived ease of use positively affects Perceived Usefulness and Attitude. Furthermore, perceived usefulness and subjective norm have positively affected on Attitude. Likewise Attitude has positively affected on Actual Use. This study reveals that employees tend to comply the peersâ€™ opinion on using transaction processing system. For future research is expected to expand the TAM model by adding external variables and individual characteristics as a moderator variableÂ Â